Integration of single-cell RNA and bulk RNA sequencing revealed malignant ductal cell heterogeneity and prognosis signatures in pancreatic cancer - Du, Haiyang; Si, Gao; Si, Jiqing; Song, Xuejie; Si, Fuchun (Frontiers in Immunology, 2025)
IntroductionPancreatic cancer is a highly malignant tumor of the digestive system with a dismal prognosis. Despite advances in diagnosis and treatment, overall survival remains extremely low. Early diagnostic markers and an improved understanding of tumor-microenvironment interactions are essential for developing more effective therapies.MethodsWe analyzed 74 single-cell RNA sequencing (scRNA-seq) samples, performing unsupervised clustering and marker-gene expression profiling to define major cell types. Large-scale chromosomal copy-number variation (CNV) analysis distinguished malignant from non-malignant ductal cells. Non-negative matrix factorization (NMF) identified stage-associated gene modules, which were integrated with TCGA bulk-RNA data and machine-learning feature selection to pinpoint candidate prognostic genes. Two independent cohorts were used for validation. Regulatory network inference (pySCENIC) and ligand–receptor interaction analysis (CellPhoneDB) explored cross-talk between malignant cells and macrophages. Finally, in vitro knockdown of CTSV assessed its functional role in pancreatic cancer (PAC) cell proliferation and migration.ResultsThree prognosis-related genes—ANLN, NT5E, and CTSV—were selected based on their strong association with clinical stage and validated in external datasets. High expression of these genes correlated with poorer overall survival and an increased infiltration of M0 macrophages. CellPhoneDB predicted significant interactions between high-expression malignant ductal cells and M0 macrophages via CXCL14–CXCR4 and IL1RAP–PTPRF axes, with SPI1 identified as an upstream regulator of IL1RAP. In vitro CTSV knockdown significantly inhibited PAC cell proliferation and migration.DiscussionOur integrative single-cell and bulk-RNA workflow identifies ANLN, NT5E, and CTSV as novel prognostic biomarkers in pancreatic cancer and highlights a pro-tumorigenic interaction between malignant ductal cells and macrophages. Targeting CTSV or disrupting CXCL14–CXCR4 and IL1RAP–PTPRF signaling may offer new therapeutic avenues for PAC.